Revision of the genus Shizuka Matsumura with description of five new species (Hemiptera: Fulgoroidea: Derbidae) - Chen, Weiqiang; Wang, Yinglun; Zhang, Yalin (Zootaxa, 2025)
The genus Shizuka in the tribe Zoraidini is revised with a reinterpretation of the tegminal venation proposed. Five new species, S. apicula sp. nov., S. neoapicula sp. nov., S. trizona sp. nov., S. paratrizona sp. nov. and S. menglaensis sp. nov. are described and illustrated. A checklist and a key to species of the genus Shizuka is provided. The characteristics of tegminal venation and metatibiotarsal formula of the genus are discussed.